EARLY DETECTION OF DIABETES MELLITUS USING RANDOM FOREST ALGORITHM - Andri Triyono; Rahmawan Bagus Trianto; Dhika Malita Puspita Arum (Julia: Jurnal Ilmu Komputer An Nuur, 2021)
Diabetes mellitus is a deadly disease. Patients with this disease often do not realize that they are improving their diabetes mellitus. It is necessary to do early prevention in order to reduce the sudden death rate of people with diabetes mellitus. In addition, during the COVID-19 pandemic, which increases the risk of death for people with comorbid diabetes mellitus. A system model for the prediction of diabetes mellitus is needed for early diagnosis of this disease. By using machine learning techniques using the Random Forest algorithm and Information Gain can be used to predict diabetes mellitus. This model has a fairly high level of accuracy, which is 98.27%, precision is 97.69% and recall is 98%.